Immunophenotypic Characterisation Along with Aberrant Expression of CD markers in Morphologically Diagnosed Cases of Acute Myeloid Leukemia (Journal of Medicine, 2022)
Immunophenotyping of leukemia cells is useful for detecting leukemia cell line, determining maturation stage and identifying aberrant antigens which act for individual treatment monitoring and detection of residual disease. A total of 104 newly diagnosed cases of acute myeloid leukemia were identified at hematology department in National Institute of Cancer Research and Hospital from January 2020 to December 2021.We detect Immunophenotypic pattern in newly diagnosed cases of acute myeloid leukemia. We also determine the frequency and pattern of aberrant expression of CD markers in acute myeloid leukemia patients. Mean age of patients was 35 years (SD±16 years) with male to female ratio was 1.53:1. Most frequent morphologic subtype was AMLM2 constituting 33.6% of all AML cases. Lineage specific markers HLADR, CD13, CD33, MPO, CD117 and CD34 were expressed in 80%, 89%, 95%, 77%, 74% and 62% cases of all AML cases respectively. Among 104 AML patient, aberrant CD expression was observed in 36% cases. The most frequently observed aberrant markers were CD7 and CD19 lymphoid markers, that were expressed in 15.38% and 14.42% cases respectively. Less frequent aberrant cCD3, CD10, CD5 and cCD79a antigens were expressed in 2.88%, 1.92%, 0.96% and 0.96% cases respectively. Immunophenotyping is essential in diagnosis and sub-classification of AML and expression of aberrant CD antigens is common in acute myeloid leukemia. These findings suggest the necessity for a more extensive study to evaluate the prognostic significance of aberrant CD marker expression in AML and to improve the accuracy of diagnosis and classification of AML.J MEDICINE 2022; 23: 106-111